Kreuzenstein - Nierhaus, Andreas (Böhlau, 2021)
Kreuzenstein Castle was built between 1874 and 1906 on the ruins of a medieval fortress. It was conceived as a family mausoleum and venue for preserving and displaying the owner’s collection of medieval art, but it can also be interpreted as the idealized vision of a medieval castle from the perspective of the 19th century. This study clarifies to what extent our view of the medieval castle is contingent on the faults, fractures and “constructs” of modernity.